Argentine social anthropology and sociology: Disciplinary identities in four conferences - Baranger, Denis (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2010)
This paper deals with social anthropology and sociology in their current state in Argentina. Beginning with a commentary about the relationship between those disciplines, and on their institutionalization in Argentina since 1957, then is performed a Principal Component Analysis [PCA] on the presentations at four scientific meetings, concerning the structure of their theoretical and methodological framework, as one of the main dimensions of the differentiation of disciplines. The results show an overlap of references important enough as to conceive that the reasons for the difference between those disciplines are hardly related to epistemology, methodology or theory. Finally, drawing on ideas from Abbott and Passeron, is discussed the possibility of a single community of social scientists